2019
DOI: 10.3168/jds.2019-16413
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation and oxidative stress transcription profiles due to in vitro supply of methionine with or without choline in unstimulated blood polymorphonuclear leukocytes from lactating Holstein cows

Abstract: Neutrophils are the most important polymorphonuclear leukocytes (PMNL), representing the front-line defense involved in pathogen clearance upon invasion. As such, they play a pivotal role in immune and inflammatory responses. Isolated PMNL from 5 mid-lactating Holstein dairy cows were used to evaluate the in vitro effect of methionine (Met) and choline (Chol) supplementation on mRNA expression of genes related to the Met cycle and innate immunity. The target genes are associated with the Met cycle, cell signal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 51 publications
3
26
0
Order By: Relevance
“…The recent work by Lopreiato et al (2019) investigated the effects of incubating bovine PMNL with Met and/or choline and observed that supplemental Met coupled with adequate choline enhanced gene expression of TLR2 and L-selectin ( SELL ), which are pathogen recognition mechanisms. In the same experiment, cells incubated without choline had greater mRNA abundance of IL1B , IL6 , IL10 , and myeloperoxidase ( MPO ), glutathione reductase ( GSR ), GSS , cystathionine gamma-lyase ( CTH ), and cysteine sulfinic acid decarboxylase ( CSAD ), indicating greater inflammation and oxidative stress; this effect, however, was ameliorated by supplementing additional Met ( Lopreiato et al, 2019 ). Thus, the increased DMI and milk production observed when feeding RPM can be partly explained by a reduction in inflammation as it directly (at the hepatic level and by dampening the immune cell overresponse) and indirectly (reducing oxidative stress) decreases circulating pro-inflammatory cytokines.…”
Section: Aa Immune Function and Oxidative Stressmentioning
confidence: 99%
“…The recent work by Lopreiato et al (2019) investigated the effects of incubating bovine PMNL with Met and/or choline and observed that supplemental Met coupled with adequate choline enhanced gene expression of TLR2 and L-selectin ( SELL ), which are pathogen recognition mechanisms. In the same experiment, cells incubated without choline had greater mRNA abundance of IL1B , IL6 , IL10 , and myeloperoxidase ( MPO ), glutathione reductase ( GSR ), GSS , cystathionine gamma-lyase ( CTH ), and cysteine sulfinic acid decarboxylase ( CSAD ), indicating greater inflammation and oxidative stress; this effect, however, was ameliorated by supplementing additional Met ( Lopreiato et al, 2019 ). Thus, the increased DMI and milk production observed when feeding RPM can be partly explained by a reduction in inflammation as it directly (at the hepatic level and by dampening the immune cell overresponse) and indirectly (reducing oxidative stress) decreases circulating pro-inflammatory cytokines.…”
Section: Aa Immune Function and Oxidative Stressmentioning
confidence: 99%
“…Methionine supplementation may also have positive implications on immune cell function (Table 4) with increased phagocytosis from neutrophils, improved oxidative burst capacity, greater T-lymphocyte proliferation, and blood neutrophil-killing capacity [90,92,103]. Late pregnancy supply of methionine may have positive RPC rumen protected choline, RPM rumen protected methionine, TAG triacylglycerol, NEFA non-esterified fatty acids, PMNL polymorphonuclear leukocytes, TCA tricarboxylic acid cycle, APP negative acute phase protein, PON paraoxonase implications on calf development (Table 3) with greater calf body weight at birth and in the first weeks of life.…”
Section: Methioninementioning
confidence: 99%
“…Methionine supplementation may also have positive implications on immune cell function (Table 4 ) with increased phagocytosis from neutrophils, improved oxidative burst capacity, greater T-lymphocyte proliferation, and blood neutrophil-killing capacity [ 90 , 92 , 103 ]. Late pregnancy supply of methionine may have positive implications on calf development (Table 3 ) with greater calf body weight at birth and in the first weeks of life.…”
Section: Introductionmentioning
confidence: 99%
“…Clearly, physiological responses in the cow to heat stress are multifaceted. Specific to immune cells, Met coupled with choline (Chol) supplementation has been associated with an improvement in PMN responses to in vitro short-term incubations and ex vivo whole-blood LPS stimulation (Vailati-Riboni et al, 2017;Lopreiato et al, 2019). The mechanisms by which supplemental Met and Chol act to modulate the immune response and oxidative stress are linked to 1-carbon metabolism, encompassing 3 pathways that represent an interconnected route through which these nutrients affect molecular events such as protein synthesis via the mechanistic target of rapamycin (mTOR), energy metabolism, and antioxidant synthesis (Coleman et al, 2020).…”
Section: Introductionmentioning
confidence: 99%